Meta-Analysis: Risk Factor Analysis of Tuberculosis Incidence - Masrizal Masrizal; Fritiara Fritiara; Ayu Salsabila; Elsha Lukman; Imalatul Mardhiyah; Mardiah Putri Al Ghani (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Tuberculosis is an infectious disease caused by the mycobacterium tuberculosis that remains a major global health problem with an estimated 10.4 million new cases of tuberculosis each year. Pulmonary Tuberculosis is a disease that has been around for a long time and is still a major problem in the health sector. Indonesia is the second largest contributor to the increase in tuberculosis cases globally.The meta study of this analysis aims to be a guide in decision making to prevent the community from Tuberculosis transmission in the future. Statistical methods in this Meta-Analysis study was combined the selected 6 articles of quantitative research from 47,474 by finding summary value using a review manager software version 5.4.1 and using a review of articles or journals that have been published for less than 5 years and are available in an online database such as Garuda, SINTA, PubMed, and Science Direct Meta analysis indicates that smoking behavior (95% ci : 1,93-6,62; P value < 0.0001), residential density (95% cl : 1,68-24,81; P value = 0.007), and humidity of 1,934 (95% ci : 1,02-2,43; P value = 0.004) increases the chances for tuberculosis. The study concluded that all variables such as smoking behaviour, residential density, and humidity increase the likelihood of tuberculosis. It has to recommended that the decision makers on Health Office force to providing more media promotion and education to patients and their families about efforts to prevent and control TB disease is expected to prevent transmission of pulmonary tuberculosis transmission in Indonesia. Keywords: Meta-analysis, Risk factors, Tuberculosis